Evolution of transpupillary laser coagulation of the retina in the treatment of active retinopathy of prematurity: from single pulse mode to navigational support - A.V. Tereshchenko; I.G. Trifanenkova; Yu.A. Sidorova; V.V. Firsova; V.V. Shaulov (Офтальмохирургия)
Purpose. To present the development stages and results of 18 years of experience in laser technologies application for the treatment of premature infants with active ROP in the Kaluga branch of S. Fyodorov Eye Microsurgery Federal State Institution. Material and methods. Transpupillary laser coagulation of the retina (LCR) was performed in 1583 children (2537 eyes) with active ROP for the period from 2004 to 2021. LCR was carried out with various stationary laser ophthalmocoagulators. Stages 2 and 3 of active ROP with an unfavorable disease course, stage of early clinical manifestations, manifestation of aggressive posterior ROP were indications for laser treatment. Results.Transpupillary LCR began to be performed for children with active ROP with a stationary ophthalmic coagulator for the first time in Kaluga branch of the S. Fyodorov Eye Microsurgery in 2004. The technology of patterned LCR in active ROP was applied for the first time at domestic and international clinical practice, in the Kaluga branch of Eye Microsurgery in 2009. Pattern LCR began to be performed on the Integre Pro Scan device in 2016. Pattern with the most dense and uniform arrangement of laser applications – hexagonal – was identified. In 2021 transpupillary LCR of the avascular zone of the retina was performed in automatic mode with navigation support on the Navilas 577s laser system. It was possible to perform LCR of the avascular zone of the retina up to the dentate line in all cases. Regression of disease was achieved in 100% of cases. Conclusion. Evolution of laser technologies and the experience of their use demonstrate the high efficacy, safety and predictability of the results of laser treatment of active ROP. Modern pattern laser techniques are highly effective, safe, dosed and tissue-saving, which can serve as the basis for standardization of retinal laser coagulation technology in the treatment of active ROP.